3D-Printed Graphene Antennas and Interconnections for Textile RFID Tags: Fabrication and Reliability towards Humidity. (5th June 2017) - He, Han; Akbari, Mitra; Sydänheimo, Lauri; Ukkonen, Leena; Virkki, Johanna
Abstract : We present the possibilities of 3D direct-write dispensing in the fabrication of passive UHF RFID graphene tags on a textile substrate. In our method, the graphene tag antenna is deposited directly on top of the IC strap, in order to simplify the manufacturing process by removing one step, that is, the IC attachment with conductive glue. Our wireless measurement results confirm that graphene RFID tags with printed antenna-IC interconnections achieve peak read ranges of 5.2 meters, which makes them comparable to graphene tags with epoxy-glued ICs. After keeping the tags in high humidity, the read ranges of the tags with epoxy-glued and printed antenna-IC interconnections decrease 0.8 meters and 0.5 meters, respectively. However, after drying, the performance of both types of tags returns back to normal.